PENGARUH OPPORTUNISTIC BEHAVIOUR, LEVERAGE, FINANCIAL DISTRESS TERHADAP EARNINGS MANAGEMENT - Alfina, Claudy; Sambuaga, Elfina Astrella (Universitas Multimedia Nusantara, 2021)
Abstract” The purpose of this study is to examine the effect of opportunistic behavior, leverage, financial distress on earnings management. Samples were obtained from non-financial companies that reported financial reports in a row from 2010-2019 with a purposive sampling method, so as to obtain data as much as 232 observations. Earnings management is measured using the Kothari (2005) model, opportunistic behavior consisting of free cash flow (FCF) as measured by the Lehn & Poulsen method (1989) and profitability as measured by Return on Assets (ROA), leverage is measured by Debt Ratio and financial distress. measured by Zmijewski's (1984) model during the study period. Data were tested using multiple linear regression through the STATA program. The results showed that opportunistic behavior as proxied by profitability can increase managers' motivation towards earnings management, as well as leverage. However, opportunistic behavior as proxied by free cash flow is not in accordance with predictions, while financial distress has no significant effect on earnings management. Keywords: Earnings Management; Opportunistic Behaviour; Leverage; Financial Distress; Zmijewski Model